FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI DALAM BERMITRA DENGAN PT. SIRTANIO ORGANIK INDONESIA - Fakhruddin Yulistiono; Triana Dewi Hapsari (Universitas Sebelas Maret, 2019)
This study aims to determine the characteristics of farmers and the factors that influence the decision of farmers to partner with PT. Sirtanio Organik Indonesia. The research method used is descriptive analytic. Determination of the location of the study was done intentionally at PT. Sirtanio Organik Indonesia. The sampling method in this study uses total sampling. The data used in this study are primary data as primary data and secondary data as supporting data. Data collection techniques are carried out by observation, interviews and documentation. The results showed that the socio-economic and ecological characteristics of partner farmers PT. Organic Sirtanio Indonesia is mostly men in productive age with the same level of primary education as having family members of 3 to 4 people, having enough experience with the status of their own land but still in a narrow category and getting capital from personal funds and credit from PT. Sirtanio Organik Indonesia and the condition of land that has fulfilled the requirements to apply organic farming. Factors that significantly influence the decision of farmers to partner with PT. Sirtanio Organik Indonesia, namely age, education, land area and income.